NURSING CARE AMONG POSTPARTUM PATIENTS WITH MILIARY TUBERCULOSIS BY THE EMPLOYING CULTURAL SENSITIVITY AND PORTABLE HEPA FILTER IN INTENSIVE CARE UNIT: A CASE STUDY - Dede Wirdah Budiastuti; Agung Waluyo; Juliana GEP Massie; Maria Pele; Nisa Utami; Novi Pampalia; Qurratu Iffoura (International Journal of Nursing and Health Services (IJNHS), 2019)
Nursing care services for post-partum patients with medical diagnoses of Miliary Tuberculosis (TB) in the Adult Intensive Care Unit (ICU) require a comprehensive approach. Critical nursing care with ICU settings and the use of portable HEPA filter are employed as alternatives if the ICU does not have an isolation room. Therefore, ICU nurses must concern the patient's needs, both the socio-cultural and cultural bio psycho. Rehabilitating patients in isolation rooms or using a portable HEPA filter that makes the patient's situation isolated results in patients' uncomfortable and restless feeling. In this case, the treated patient hold Middle East culture, and thus, she concerns about covering her head as part of her religious and cultural teachings. However, wearing headgear or hijab is rarely considered in the ICU because ICU nurses prioritize the critical condition of patients as the most vital regard to consider. This case study describes how to provide care to patients in ICU with the use of portable HEPA filter as an alternative TB isolation room and a culturally sensitive approach to meet the socio-cultural needs of the patient. Therefore, she feels comfortable and safe in the ICU room. Keywords: Miliary TB, portable HEPA filter, cultural approach